Strawberry Generation: When Strawberry Parenting and Teaching Weaken Students’ Mathematical Resilience - Jayanti, Tety; Kawuryan, Sekar Purbarini (Jurnal Pendidikan Progresif, 2025)
Abstract: Strawberry Generation: When Strawberry Parenting and Teaching Weaken Students' Mathematical Resilience. Objectives: This study aims to investigate the impact of the "strawberry" parenting and teaching approach on students' mathematical resilience, focusing on how such an approach affects their ability to face challenges and adapt in learning environments. Methods: A quasi-experimental design was used, involving two groups of students in a fourth-grade class at SD Muhammadiyah Pendowoharjo. The experimental group received instruction using a growth mindset-based approach, while the control group followed the conventional "strawberry" approach. Pretests and posttests were administered to measure changes in mathematical resilience. Findings: The results revealed that the "strawberry" approach significantly hindered students' mathematical resilience. Students in the experimental group, who were taught using a growth mindset approach, demonstrated better adaptability and problem-solving skills. In contrast, students in the control group struggled with challenges and showed lower levels of resilience. Conclusion: The study highlights the importance of shifting from a protective, overly supportive approach to one that challenges students and encourages growth. Adopting methods that foster resilience, such as problem-based learning, can significantly improve students' mathematical resilience and confidence in learning. Keywords: mathematical resilience, strawberry parenting, growth mindset, problem-based learning, student adaptability, teaching strategies.